Rancang Bangun Sistem Informasi Akademik Berbasis Website Pada SMP Negeri 4 Bangkalan - Achmad Faishal; Dr. M.J. Dewiyani Sunarto; Norma Ningsih (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
Bangkalan Middle School 4 is an educational institution that was established in 1979 and is one of the public schools. During this time, Bangkalan 4 Public Middle School recorded and carried out the assessment process using paper, where the recording of values and presence carried out on paper sometimes suffered loss or damage to the paper and in the process of calculating the value is still done manually which results in miscalculation or typing in the delivery of information about the school's academic activities is not good enough, delivered at the end of the semester. To overcome this problem, 4 Bangkalan Middle School requires the School Academic Information System to be related to student attendance, student assessment and attendance information, grades and student ranking. So that the school can provide academic information to students and parents of students. Based on the results of the analysis, system design, and making that has been done, it can be concluded that the design of academic information systems can record the presence of students by homeroom and can be seen directly by students without having to wait at the end of the semester. a matter of minutes without having to count the grades of students one by one. The system will calculate the value automatically and can be directly seen by homerooms and students without having to wait 1 week to 1 month. Students can also find out student grade ranking information.